The Development of Financial Inclusion and Digital Financial Literacy in Indonesia - Salsiati (Journal of Multi-Disciplines Science, 2025)
As many as 32%, or 76 million people, have not been touched by financial services. This study aims to explain the development of financial inclusion and digital financial literacy in Indonesia. This study was compiled using qualitative methods. This study uses a descriptive approach and a literature study. Data were obtained from journal literature, books, and policy documents. The results of this study indicate that the achievement of financial inclusion in 2016 was 67.80%, and in 2019, it increased to 76.19%. The digital financial literacy index 2016 reached 29.70% and increased in 2010 to 38.03%. This shows that out of every 100 people there are around 38 people who are well literate. The government's role is crucial, but it's not a one-man show. It needs to provide encouragement and support to various entities, both government, private, and third sectors. Only through a collaborative effort can we overcome the various challenges and optimize financial inclusion and digital financial literacy programs in Indonesia.